Jurnal English - Lin Yan Syah; Dedi Rianto Rahadi; M Mifta Farid (Management and Leadership Study Programme, 2022)
Indonesia's domestic market, which is a very broad market with a very dense total population which can be estimated at around 270 million people (BPS, 2021). Such a large domestic market can push the possibility of forming a strong competition or competition between imported products and local products. Increasing local brands is a strategic step that is useful to show or introduce Indonesian-made products to the global market. The purpose of this research is to understand the attitudes of Generation Z consumers towards local and imported fashion brands. The research methodology uses a descriptive qualitative approach. Data collection using questionnaires can be explained according to student behavior on the use of local fashion brands and imported fashion. In Generation Z, both men and women, do not tend to buy imported fashion products, do not tend to buy the latest imported brand brand clothes, do not agree to buy different imported brand products with the same quality and lack confidence in wearing imported fashion brand clothes, but like to buy product clothes quality imports. With the quality of the product, it can be the first benchmark in product evaluation and this also depends on the attitude of the consumer. The results of the study explain that Generation Z men and women, tend to buy local fashion products, tend to buy the latest local brand clothing models, like to buy quality local clothes, often buy different local brand products but the quality is the same and are more confident by wearing fashion clothes. local brands. So it can be concluded that most of Generation Z are more likely to buy local brand fashion products. And for the quality of local products, you can say that they are not far behind imported products, so it can be said that local products can compete with imported products.